Indirect pulp capping in primary molar using glass ionomer cements - Murtia Metalita; Udijanto Tedjosasongko; Prawati Nuraini (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Indirect pulp capping in primary teeth, however, is more rarely conducted than permanent teeth, since it thought to have low impact and most suggestion is for taking caries lesion aggressively on primary teeth. Purpose: The study was aimed to evaluate the subjective complaint, clinical symptom, and radiographic appearance of indirect pulp capping treatment using glass ionomers cements in primary molar. Methods: Sixteen children in range of age 6 to 8 years old, who visited Clinic of Pediatric Dentistry Universitas Airlangga Dental Hospital, Surabaya Indonesia, were the subject of study. They had one occlusal dental caries on one side of maxillary or mandibular primary molar with the diagnose of pulpitis reversible. The experimental group, had indirect pulp capping treatment with glass ionomer cements (GC Fuji VII®), while the control group, had indirect pulp capping treatment with calcium hydroxide (Metapaste). Each group was filled with GC Fuji IX® as permanent restoration. After one week, one month, and three months later, the observations were made on subjective complaint, clinical symptom, and radiographic appearance. Results: The results showed no subjective complaint such as pain or problem on mastication; no negative clinical symptoms such as pain on palpation, gingivitis or periodontitis, and abnormal tooth mobility; no negative radiographic appearance such as pathological apical radioluscency, internal or external resorbtion, and change of ligament periodontal widthafter the treatment. Conclusion: The study suggested that indirect pulp capping treatment using glass ionomer cement materials on primary teeth might be considered to be the treatment choice.Latar belakang: Indirect pulp capping pada gigi sulung lebih jarang dilakukan dibandingkan gigi permanen, karena dianggap memiliki dampak yang rendah dan sebagian besar menyarankan untuk mengambil lesi karies secara agresif pada gigi sulung. Tujuan: Penelitian ini bertujuan untuk mengevaluasi keluhan subjektif, gejala klinis, dan gambaran radiografi perawatan indirect pulp capping menggunakan glass ionomer pada gigi molar sulung. Metode: Enam belas anak berusia 6 sampai 8 tahun, yang mengunjungi Klinik Kedokteran Gigi Rumah Sakit Gigi dan Mulut Universitas Airlangga, Surabaya Indonesia, adalah subjek penelitian ini. Mereka punya satu karies gigi oklusal molar sulung pada satu sisi maksila atau mandibula dengan diagnosa pulpitis reversibel. Pada kelompok eksperimen dilakukan perawatan indirect pulp capping dengan glass ionomer (GC Fuji VII®), sedangkan kelompok kontrol, dilakukan perawatan indirect pulp capping dengan kalsium hidroksida (Metapaste). Setiap kelompok ditumpat dengan glassionomer untuk gigi posterior (GC Fuji IX®) sebagai restorasi permanen. Observasi dilakukan setelah satu minggu, satu bulan, dan tiga bulan kemudian, pengamatan dilakukan pada keluhan subjektif, gejala klinis, dan gambaran radiografi. Hasil: Hasil penelitian menunjukkan tidak ada keluhan subjektif seperti rasa sakit atau masalah pada pengunyahan; tidak ada gejala klinis negatif seperti rasa sakit pada palpasi, gingivitis atau periodontitis, dan mobilitas gigi abnormal; tidak ada gambaran radiografi negatif seperti radioluscency patologis apikal, resorbsi internal atau eksternal, dan pelebaran periodontal ligamen setelah perawatan. Simpulan: Penelitian ini menunjukkan bahwa perawatan indirect capping menggunakan glass ionomer pada gigi sulung dapat dipertimbangkan sebagai pilihan perawatan.